ANALISIS KEMUNGKINAN TERJADINYA KONDENSASI PADA PIPA ALIR UAP DARI SEPARATOR KE SCRUBBER BERDASARKAN MODEL PENURUNAN TEKANAN PADA PLTP AREA LAHENDONG UNIT 5 & 6 - Brenda Bella Gunena; Djeli Alvi Tulandi; Jeferson Polii (Charm Sains: Jurnal Pendidikan Fisika, 2021)
Geothermal production in steam turbines must pay attention to the quality of the incoming steam because if their steam is condensed it will affect the effectiveness of the turbine, so the purpose of this study is to examine the possibility of condensation in the pipe steam flow. The method used in this research is descriptive, where each parameter measurement is calculated using Microsoft Office Excel programming steam prog and using the Harrison and Friston equation which calculates per segment of pipe length (3 m) and calculates the vapor fraction (x) and pipe length in a graph which determines the final result of this study. The graph results between the vapor fraction and the length of the pipe show that the vapor fraction value along the steam pipe continues to increase until 0.9997 (99.98%) almost becomes 1 (100%) meaning that there is no condensation in the steam pipe from the separator to the scrubber.